Time in Sport Pedagogy: A Review of the Evidence (International Journal of Innovative Research in Computer Science & Technology, 2020)
This article offers a comprehensive  overview of the existing literature in sport pedagogy on  time-related studies. The research is organized and  analyzed into four categories: how time is conceived, how  time is measured, what is known about how time is used in  physical education and sport contexts, and what is still  unknown about time-related activities. In the part, a six point agenda for extending and continuing time research in  sport pedagogy is proposed. Sport pedagogy is a branch of  sport science concerned with educational processes  including exercise, movement, play, and sport.  Traditionally, structured physical education in schools has  been emphasized with the aim of promoting children's and  teenagers' growth and enabling them to engage in a range  of sports and movement cultures. As a result, sport  pedagogy and sport didactics are inextricably linked. There  is no question that a serious, contributing science of sport  pedagogy has only been present for a few years, regardless  of how one defines it or whether one wishes to include or  omit specific aspects of it.
Keywords: Education; Physical Education; Scientific Community; Sports Pedagogy; Time Management